Filsafat Eksistensialisme yang Dianut oleh Iwan Simatupang Melalui Karya Bulan Bujur Sangkar: Pendekatan ekspresif: The Existentialist Philosophy Embraced by Iwan Simatupang Through His Drama Script ‘Naskah Drama Bulan Bujur Sangkar’: An Expressive Approach - Izzati, Hanifah; Layaly, Fikriyah; Erowati, Rosida (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study discusses the application of existentialism philosophy to the Bulan Bujur Sangkar manuscript embraced by Iwan Simatupang and describes Iwan Simatupang's social background which proves the existence of an existentialist philosophy school. This research uses a descriptive qualitative method with an expressive approach to represent the author's emotions and messages in his work. The object of this research is the script of the drama Bulan Bujur Squarer by Iwan Simatupang. The collection technique in this study is a literature study. For the technique of analyzing data, use the technique of watching and taking notes. The results of the discussion found that the philosophy of existentialism embraced by Iwan Simatupang in the Bulan Bujur Sangkar Manuscript was proven in intrinsic and extrinsic elements. It is evident in the analysis of Iwan Simatupang's existentialism which is reflected in the figure of the Parents. The ideology of the Old Man who has a free life of thought, has no boundaries like existentialism that upholds freedom of thought and action accompanied by responsibility.